Spectrum of SCN8A-Related Epilepsy - Morgan, Lindsey A (Pediatric neurology briefs, 2015)
Investigators from the EuroEPINOMICS European research consortium studied 17 patients with epileptic encephalopathy due to SCN8A mutations and reported the specific genetic and phenotypic features